A PRAXEOLOGICAL ANALYSIS OF PRE-SERVICE ELEMENTARY TEACHER-DESIGNED MATHEMATICS COMICS - Zetra Hainul Putra; Dahnilsyah Dahnilsyah; Ayman Aljarrah (Journal on Mathematics Education, 2021)
Mathematical and didactic knowledge presented in mathematics textbooks and other resources, like mathematics comics (MCs), needs to be evaluated from a lens of appropriate theoretical framework in mathematics education before it can be used as a medium for teaching and learning mathematics.Therefore, this study investigates mathematical and didactic competencies that were reflected in MCs designed by pre-service elementary teachers. The framework for analysing mathematical knowledge embedded in these MCs is based on the Anthropological Theory of the Didactic, specifically a praxeology. This study utilized a content analysis technique within a qualitative approach. Thirteen MCs were analysed using a praxeological analysis; the type of task and techniques (praxis block) as well as the possible technology and theory (logos block). The findings demonstrate that the mathematical praxeologies embedded in MCs belong to five mathematical domains, namely numbers and operations; number theory; fractions, decimals, and percentages; ratio and proportion; as well as measurement. Additionally, the analysis revealed that seven of these MCs were related to a single domain, while the others belong to two or three mathematical domains. Concerning the mathematical praxeologies, most of MCs focus on presenting the practical blocks, the type of task and the techniques, while only a few could provide the theoretical lens to justify the practical blocks.